Population structure, admixture, and aging-related phenotypes in African American adults: the Cardiovascular Health Study. - Reiner, Alexander P; Ziv, Elad; Lind, Denise L; Nievergelt, Caroline M; Schork, Nicholas J; Cummings, Steven R; Phong, Angie; Burchard, Esteban González; Harris, Tamara B; Psaty, Bruce M; Kwok, Pui-Yan (Am J Hum Genet, 2005)
U.S. populations are genetically admixed, but surprisingly little empirical data exists documenting the impact of such heterogeneity on type I and type II error in genetic-association studies of unrelated individuals. By applying several complementary analytical techniques, we characterize genetic background heterogeneity among 810 self-identified African American subjects sampled as part of a multisite cohort study of cardiovascular disease in older adults. On the basis of the typing of 24 ancestry-informative biallelic single-nucleotide-polymorphism markers, there was evidence of substantial population substructure and admixture. We used an allele-sharing-based clustering algorithm to infer evidence for four genetically distinct subpopulations. Using multivariable regression models, we demonstrate the complex interplay of genetic and socioeconomic factors on quantitative phenotypes related to cardiovascular disease and aging. Blood glucose level correlated with individual African ancestry, whereas body mass index was associated more strongly with genetic similarity. Blood pressure, HDL cholesterol level, C-reactive protein level, and carotid wall thickness were not associated with genetic background. Blood pressure and HDL cholesterol level varied by geographic site, whereas C-reactive protein level differed by occupation. Both ancestry and genetic similarity predicted the number and quality of years lived during follow-up, but socioeconomic factors largely accounted for these associations. When the 24 genetic markers were tested individually, there were an excess number of marker-trait associations, most of which were attenuated by adjustment for genetic ancestry. We conclude that the genetic demography underlying older individuals who self identify as African American is complex, and that controlling for both genetic admixture and socioeconomic characteristics will be required in assessing genetic associations with chronic-disease-related traits in African Americans. Complementary methods that identify discrete subgroups on the basis of genetic similarity may help to further characterize the complex biodemographic structure of human populations.
Keywords: African Americans; Aged; Aging; Algorithms; Cardiovascular Diseases; Cohort Studies; Female; Genetics, Population; Genotype; Humans; Male; Models, Genetic; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Socioeconomic Factors